Stock Control Management Practices and Performance of the Kenya Electricity Generating Company in Eastern Region, Kenya - Njeru, Ngari; Osoro, Anthony (International Journal of Supply Chain Management, 2024)
Purpose: The purpose of this study was to establish the relationship between Stock Control Management Practices and Performance of the Kenya Electricity Generating Company in Eastern Region, Kenya. The specific objectives of this study were; Inventory Optimization, Economic Order Quantity, Safety Stock Levels and Tracking Stock respectively. Methodology: The study employed a descriptive research design. The study preferred this method because it allows an in-depth study of the subject. The target population of this study was 274 respondents from Kenya Electricity Generating Company in Eastern Region, Kenya. Data was collected using self-administered questionnaires. Pilot study was carried out to establish the validity and reliability of the research instruments. The instruments were designed appropriately according to the study objectives. The data collected was analyzed by use of descriptive and inferential statistics. The study used multiple regression and correlation analysis to show the relationship between the dependent variable and the independent variables. The data generated was keyed in and analyzed by use of Statistical Package of Social Sciences (SPSS) version 28 to generate information which was presented using tables, frequencies and percentages. Reliability of the research instruments was done to validate the pilot test for confirmation of the presence of clear questionnaire in relation to reliability and validity of the designed instruments. Data was presented in form of tables. Findings: The study confirmed a strong relationship between Stock Control Management Practices and Performance of the Kenya Electricity Generating Company in Eastern Region, Kenya; hence the need to implement the study findings. Unique Contribution to Theory, Practice and Policy: The study was anchored on inventory theory. The study recommends implementation of Inventory Optimization, Economic Order Quantity, and Safety Stock Levels and Tracking Stock management practices to improve performance of Kenya Electricity Generating Company in Eastern Region, Kenya. That in future, different counties, sectors and organizations need to strengthen their performance and procurement processes with the help of Inventory optimization, EOQ, Safety Stock Levels and Tracking Stock management practices.